Effects of Calorific Value of Pine Wilt Infected Trees on the Spread of Wildfire - Hyuk, Kwon; Ha Sung, Kong, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study was aimed to analyze the effects of pine wilt infected trees on the spread of wildfire measuring water content and calorific value by piling up terms of infected trees. The test results are as follows. First, little difference of water content was found by piling up terms among 5 samples of pine wilt infected trees over 4 years and less than 5 years, showing 19.8% of mean value with not more than 8% of deviation, which is about one sixth compared to the water content of domestic live pine trees 115%. Second, calorific value of pine wilt infected trees showed the mean value of 4860kcal/kg ranging from 4680kcal/kg at the samples over 3 years and less than 4 years up to 5340kcal/kg at the samples over 1 year and less than 2 years, reflecting beyond the mean value of general pine trees. Lastly, with respect to the effects of calorific value of pine wilt infected trees on the spread of wildfire, the factors to affect the spread of large-scale fire were sufficient oxygen, infected piled trees which are inflammables, colonies of pine trees, strong wind, pine resin, and so on, regardless of piling up terms.